Analisis Proximate (Moisture in Analysis dan Volatile Matter) dan Kadar Sulfur pada Batubara - Jounza, Naomi Rahma Dania; Amran, Ali (Lembaga Yasin AlSys, 2026)
Coal quality testing is important to determine fuel characteristics before use for industrial purposes. This study aims to analyze the values of Moisture in Analysis, Volatile Matter, and total sulfur content in coal samples through laboratory practice at PT SUCOFINDO Padang Branch. This study used a quantitative descriptive approach with a laboratory practice method. Data were collected through duplicate testing of coal samples using an oven, VM furnace, sulfur furnace, analytical balance, desiccator, aluminum crucible, Volatile Matter crucible, and sulfur crucible. The results showed that the Moisture in Analysis values in the coal samples were 27% and 22%, with an average of 24.5%. The Volatile Matter values obtained were 81% and 66%, with an average of 73.5%. Meanwhile, the results of total sulfur content analysis showed the same value in the two replications, namely 1.67%. These findings indicate that the coal samples had relatively high moisture and volatile matter contents, as well as sulfur content that needs attention because it may affect combustion efficiency, industrial equipment, and the environment. The conclusion of this study confirms that proximate analysis and sulfur content testing play an important role as a basis for assessing coal quality in industrial laboratories. The practical contribution of this study lies in strengthening understanding of coal quality testing procedures that are relevant to supporting the evaluation of industrial fuel quality.